2013
DOI: 10.3928/01477447-20130122-27
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Dimensions and Morphological Study of the Lumbar Spinal Canal in the Normal Egyptian Population

Abstract: Information regarding the precise dimensions of the lumbar vertebrae is essential for spinal surgery and instrumentation. When stenosis of the vertebral canal or the intervertebral foramen exists, the neural structures in them can be affected and cause symptoms such as low back or radicular pain. Accurate and comprehensive spinal canal measurements in the lumbar vertebrae are incomplete. The purpose of this study was to collect data on the dimensions of the lumbar spinal canal from computed tomography scans. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
3
15
2
1
Order By: Relevance
“…Concerning the IPD, our study showed a progressive increase from L1 to L5. Tarek et al [6] and Ongolo Zogo et al [9] found respectively in Egyptians and in Cameroonians similar results. On the other hand, El-Rakhawy et al [8] noticed an average IPD almost identical at the level of the four first lumbar vertebrae (≈ 24mm) followed by an increase in L5 (28.48mm).…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)supporting
confidence: 73%
See 4 more Smart Citations
“…Concerning the IPD, our study showed a progressive increase from L1 to L5. Tarek et al [6] and Ongolo Zogo et al [9] found respectively in Egyptians and in Cameroonians similar results. On the other hand, El-Rakhawy et al [8] noticed an average IPD almost identical at the level of the four first lumbar vertebrae (≈ 24mm) followed by an increase in L5 (28.48mm).…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)supporting
confidence: 73%
“…The lower value was found in L3. The same remark was made by Amonoo-Kuofi et al [5] in Nigeria, by Tarek Aly et al [6] in Egypt, and by Lee et al [7] in Corea. The high APD in L1 and L2 could be explained by the bulge of the conus medullaris at this level.…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)supporting
confidence: 51%
See 3 more Smart Citations